2004
DOI: 10.1152/japplphysiol.01367.2003
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate shuttling during rest and exercise before and after endurance training in men

Abstract: We describe the isotopic exchange of lactate and pyruvate after arm vein infusion of [3-(13)C]lactate in men during rest and exercise. We tested the hypothesis that working muscle (limb net lactate and pyruvate exchange) is the source of the elevated systemic lactate-to-pyruvate concentration ratio (L/P) during exercise. We also hypothesized that the isotopic equilibration between lactate and pyruvate would decrease in arterial blood as glycolytic flux, as determined by relative exercise intensity, increased. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
53
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 46 publications
4
53
1
Order By: Relevance
“…Nominal arterial lactate concentration is 1 mM and is typically higher in the venous effluent of resting muscle due to ongoing glycolysis (12,87). As well, lactate is highly soluble in body water and rapidly transits cell membranes via a family of monocarboxylate transport (i.e., MCT) proteins that are expressed in plasma (28,30,61,85,196), mitochondrial (28,30,35,61,82,83,85), and peroxisome membranes (138).…”
Section: The Dynamic Range Of Lactate Signaling In Activation Of the mentioning
confidence: 99%
See 1 more Smart Citation
“…Nominal arterial lactate concentration is 1 mM and is typically higher in the venous effluent of resting muscle due to ongoing glycolysis (12,87). As well, lactate is highly soluble in body water and rapidly transits cell membranes via a family of monocarboxylate transport (i.e., MCT) proteins that are expressed in plasma (28,30,61,85,196), mitochondrial (28,30,35,61,82,83,85), and peroxisome membranes (138).…”
Section: The Dynamic Range Of Lactate Signaling In Activation Of the mentioning
confidence: 99%
“…In contrast, IL-6 exists in nanomolar or picomolar concentrations, is released from muscle by unknown mechanisms, and circulates bound to plasma proteins. During physical exercise, lactate concentration can exceed 10 mM, and the lactate/ pyruvate ratio can exceed 100 during vigorous exercise (87). Furthermore, it is clear that the concentrations of lactate and pyruvate can change as blood courses through metabolically active tissues, reflecting an interplay between cell metabolism and substrate delivery in the signaling process (101,102).…”
Section: The Dynamic Range Of Lactate Signaling In Activation Of the mentioning
confidence: 99%
“…This was based on existing literature, which showed that the majority of 3-carbon-unit release from exercising muscle was lactate, with concurrent pyruvate release being minor in comparison (1,2,7,9). However, after reading the 2004 Henderson et al paper (5) with much interest, which reported that working muscles released the same amount of lactate and pyruvate, we decided that both metabolites must be measured in order to get an accurate estimate of total carbohydrate-derived 3-carbon-unit release across the exercising muscle. However, contrary to Henderson et al (5), we found nearly a fivefold greater net lactate release during exercise compared with pyruvate release.…”
mentioning
confidence: 99%
“…When one methodically studies the paper from Henderson et al (5), and their related paper that was published five years earlier (3), it becomes apparent that there are several ambiguous statements regarding the time course of their pyruvate and lactate release data, and there appear to be several methodological errors. First, since there are fluid shifts occurring between muscle and the vascular space during exercise, plasma protein, hemoglobin, and hematocrit are often used to provide a measure of relative changes in intravascular volume when applying the Fick equation.…”
mentioning
confidence: 99%
See 1 more Smart Citation